1979
DOI: 10.1002/1097-4679(197904)35:2<270::aid-jclp2270350210>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of process-reactive measures in schizophrenia

Abstract: Studied 12 measures of process-reactive schizophrenia to determine their relative effedveness in predicting outcome defined as symptomatic improvement. Each patient ( N = 144) was rated on the process-reactive measures and a t 3-and 6-month intervals on the Present State Examination to evaluate symptom change. Major findings were that the Ego-Strength, St.age of Illness, Kantor, Langfeldt, paranoid and chronicity criteria failed to predict outcome successfully. The first four criteria do not appear to be suita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…When we look at studies of the process-reactive dimension as a predictor of outcome, we find that the recent results have been mixed (Higgins 1971; Evans et al 1973; Bromet et al 1974; Strauss and Carpenter 1974; Herron 1979; Schultz and Herron 1979; Cheselka et al 1984; Westermeyer and Harrow 1984; Harrow and Quinlan 1985; Harrow et al 1986). These mixed results suggest that the process-reactive dimension does have prognostic utility, but this utility may be limited.…”
Section: Do Narrow Concepts Of Schizophrenia Such As That Found In Th...mentioning
confidence: 88%
“…When we look at studies of the process-reactive dimension as a predictor of outcome, we find that the recent results have been mixed (Higgins 1971; Evans et al 1973; Bromet et al 1974; Strauss and Carpenter 1974; Herron 1979; Schultz and Herron 1979; Cheselka et al 1984; Westermeyer and Harrow 1984; Harrow and Quinlan 1985; Harrow et al 1986). These mixed results suggest that the process-reactive dimension does have prognostic utility, but this utility may be limited.…”
Section: Do Narrow Concepts Of Schizophrenia Such As That Found In Th...mentioning
confidence: 88%
“…The following comments are in response to a study by Harrow et al (1986). Results of two studies (Schultz and Herron 1979; Cheselka et al 1984) preceding but not mentioned by Harrow et al forecasted a number of their current findings. In particular, we established the predictive ability of the Phillips scale and marital status for symptom improvement in schizophrenic patients diagnosed by DSM-II (American Psychiatric Association 1968).…”
mentioning
confidence: 83%
“…Considerable research in support of this view has been reported on some of these, such as premorbid adjustment and symptom patterns (Herron, 1977;Schultz & Herron, 1979), but the need remains for exploration of the more complex and subtle possible antecedents, such as defense mechanisms. Considerable research in support of this view has been reported on some of these, such as premorbid adjustment and symptom patterns (Herron, 1977;Schultz & Herron, 1979), but the need remains for exploration of the more complex and subtle possible antecedents, such as defense mechanisms.…”
Section: Rockland Psychiatric Centermentioning
confidence: 99%